Humanity. A medical student's reflections on the healer role - Imcaoudene, Ahmed (The International Journal of Whole Person Care, 2022)
Detailing the moving story of his interactions with a patient and her significant other, Ahmed Imcaoudene's Goodwin Prize-winning essay on the Healer Role was selected for presentation in McGill University's Physicianship curriculum. It was also read at the 4th International Congress on Whole Person Care on October 22nd, 2021, introducing profound discussions on compassion in healthcare.